Th1/Th2-type cytokine profile in C57 black mice inoculated with live Echinococcus granulosus protoscolices - Shahla Rostami-Rad; Rasool Jafari; Hossein Yousofi Darani (Elsevier, 2018)
Background and objective: Cystic echinococcosis (CE) is a widespread parasitic disease caused by infection with the larval stage of a tapeworm, Echinococcus granulosus. The immune response to hydatid cyst in intermediate hosts is a complex and contradictory issue. It is suggested that a Th2 response would favor the establishment of the parasite, whereas a Th1 response would be lethal for the parasite. Thus, the aim of the present study was to evaluate the levels of IL2, TNFα, and IFNγ as T helper (Th)1-type cytokines, IL4 as a Th2-type cytokine, and total IgG in C57/black mice inoculated with E. granulosus protoscoleces (PSCs). Materials and method: In this experimental study, six C57/black mice were intraperitoneally inoculated with live E. granulosus PSCs and a control group consist of six C57/black mice received normal saline. The quantitative concentrations of IL2, TNFα, IFNγ, and IL4 were determined in the first, second, fourth, eighth and 12th-week post inoculation in both case and control groups. Results: The results showed that at the early post-infection phase (3-4 weeks) the Th1-type cytokine profile was predominant, however the shift to Th2-type cytokine took place in the 4th week. Conclusion: Based on the results of the present study, we can suggest that the shift from Th1 to Th2 reactivity may be associated with persistent of the disease because Th2 reactivity may be less effective than Th1 reactivity in countering the parasite. Keywords: Echinococcus granulosus, T helper, Immune response, C57/black